OS SOLUBILITY IN SILICATE MELTS: NEW EFFORTS AND RESULTS - Borisov A.; Walker R.J. (My University, 2000)
New experimental results are reported on the partitioning of Os between Ni94Os6 (at) alloys and silicate melt at 1400 °C at one atmosphere total pressure and oxygen fugacities ranging from 10−6 to 10−8 atm. Specially designed experiments allowed us to avoid nugget formation, which was responsible for the anomalously high Os solubilities reported by Borisov and Palme (1998). Experimental glasses were analyzed by instrumental neutron activation analysis and by isotope dilution analysis. Results reveal a strong dependence of Os solubility on fO2, with Os contents decreasing from about 100 ppb to about 5 ppb as fO2 decreases. The slope of log (Os solubility) vs. log fO2 implies that Os3+ is the dominant Os valence state in silicate melts. The relative geochemical behavior of Os and Pt is also compared. Results suggest that Pt is more siderophile, and may also be more chalcophile than Os under the conditions considered.